Đinh Đức Hùng
11 tháng 3 2017 lúc 16:58

\(2xy+y=1+5x\)

\(\Leftrightarrow2.2xy+2y=2+10x\)

\(\Leftrightarrow2y\left(2x+1\right)=5\left(2x+1\right)-3\)

\(\Leftrightarrow2y\left(2x+1\right)-5\left(2x+1\right)=-3\)

\(\Leftrightarrow\left(2y-5\right)\left(2x+1\right)=-3\)

\(\Rightarrow\left(2y-5\right)\left(2x+1\right)=-1.3=-3.1=1.\left(-3\right)=3.\left(-1\right)\)

Nếu \(2y-5=-1\) thì \(2x+1=3\) => y = 2 thì x = 1

Nếu \(2y-5=-3\) thì \(2x+1=1\) => y = 1 thì x = 0

Nếu \(2y-5=1\) thì \(2x+1=-3\) => y = 3 thì x = - 2

Nếu \(2y-5=3\) thì \(2x+1=-1\)=> y = 4 thì x = - 1

Vậy ( x;y ) = { (1;2) ; (0;1) ; (-2;3) ; (-1;4) }

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN